Literature Review Evaluation of Fieldwork Practice Programs in Vocational High Schools in Indonesia - Yuliyanto, Riyan; Adam Rahmanto, Andi (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2023)
In an effort to maintain and improve the quality of Vocational High School (SMK) graduates and reduce misses from the demands of the industrial world and technological advances, the government has tried to implement various policies both in terms of quantity and quality. The activities of students in an effort to increase skill competence are through Field Work Practice (PKL) activities that involve the world of work directly. But in fact, according to nationwide data from the Central Statistics Agency (BPS), in February 2023, unemployment for vocational school graduates reached 9.6%, which is the largest of the overall levels of education in Indonesia. This literature review provides a summary of the results of the PKL program evaluation by applying the Context, Input, Process, Product (CIPP) evaluation model. The results of this study prove that the program is running in accordance with the objectives with good output. However, there needs to be careful preparation and seriousness from schools and learners.